2021
DOI: 10.3389/fevo.2021.620062
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Drivers of Spatial Taxonomic and Functional Beta-Diversity of British Breeding Birds

Abstract: Spatial variation in community composition may be driven by a variety of processes, including environmental filtering and dispersal limitation. While work has been conducted on the relative importance of these processes on various taxa and at varying resolutions, tests using high-resolution empirical data across large spatial extents are sparse. Here, we use a dataset on the presence/absence of breeding bird species collected at the 10 km × 10 km scale across the whole of Britain. Pairwise spatial taxonomic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 111 publications
(141 reference statements)
2
9
1
Order By: Relevance
“…Geographical distance is an important driver of beta diversity patterns in birds (Wayman et al, 2021). However, we did not find a significant influence of geographical distance on beta diversity patterns in the E or the W Himalaya.…”
Section: Limited Role Of Distance and Habitat Modificationcontrasting
confidence: 90%
See 2 more Smart Citations
“…Geographical distance is an important driver of beta diversity patterns in birds (Wayman et al, 2021). However, we did not find a significant influence of geographical distance on beta diversity patterns in the E or the W Himalaya.…”
Section: Limited Role Of Distance and Habitat Modificationcontrasting
confidence: 90%
“…We found that the different beta diversity measures were related to similar predictors within a region (i.e., E or W Himalaya). However, the relative contribution of the different predictors in explaining the variation in beta diversity differed across the different measures (Figure 5), which has been reported elsewhere (Wayman et al, 2021). Interestingly, precipitation explained a large proportion of variation in taxonomic component of beta diversity in the W Himalaya (Figure 5), but a lower proportion of variation in phylogenetic and functional component.…”
Section: Differences Between Beta Diversity Componentssupporting
confidence: 68%
See 1 more Smart Citation
“…Lennon et al, 2000;Wayman et al, 2021). Our results for native β-diversity are in full agreement with the aforementioned studies.…”
supporting
confidence: 92%
“…However, native and alien species might respond to ecological gradients in similar or opposite ways. For instance, climate, especially temperature and precipitation, and land uses are considered important—albeit of different strength—drivers of species composition of alien and native bird communities (Li et al, 2018; Sinha et al, 2022; Wayman et al, 2021; Zellweger et al, 2017), but human‐related or other factors (e.g. introduction event characteristics) and native diversity might play a role in shaping alien β‐diversity (Ascensão et al, 2020; Dyer et al, 2016; Latombe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%